Irritation test and melanin whitening cream epigallocatechin gallate green tea leaf with mexameter and self-assessment (Bangladesh Journal of Medical Science, 2023)
Background: Green tea (Camelia sinensis L.) contains flavonoids consisting of Epigallocatechin gallate (EGCG) which functions as whitening, anti-acne, antioxidant, anti-inflammatory. Previous studies have shown that EGCG with a concentration of 6% is the optimum concentration in cream formulations (Widyaningrum, 2015b). Phase One Clinical Test was conducted to determine the safety of cream preparations with irritation as a benchmark and continued to test its effectiveness as a whitening cream on 20 respondents aged 17-45 years.Material and Methods: The research method employed was the Open Test. The results of the study for 21 days after applying the EGCG anti-acne cream were assessed using a mexa-meter and self-assessment.Result: The erythema assessment showed that the preparation did not cause irritation in the absence of erythema and for the melanin assessment, the results were not significant with p Value 0.376 (